Role and place of woman in Islam - Baibosunov, D.B.; Balshikeyev, S.B.; Zhumakanova, U.S. (KU Publ., 2021)
The article deals with important issues related to the attitude to women in the Islamic world, the history of Islam and its current issues. It also seeks to address the challenges of studying the role and importance of a woman in society: in the family, as a mother, her moral values as a source of spiritual principles. The tools of this article were the Holy Quran, collections of hadiths and the biography of the Prophet Muhammad. Like men, women have a role to play in society. According to the Almighty, all the creatures he created live in pairs, and there is no one equal to God alone. Women have a key role to play in preserving and perpetuating the human race. The birth of a new generation does not guarantee that it will grow up with dignity and survive. Therefore, the upbringing of children, especially in the first years of life, is the most important task of a mother. This process requires some preparation and knowledge in various spheres of life. Muslim woman feels responsible for the household and tries to treat it in the best way possible. This article will be an interesting topic for readers.
Исламдағы əйел адамның рөлі мен орны
Роль и место женщины в исламе
Keywords: verse; woman; Islam; Quran; Prophet; Surah; Hadith